Visualization of the Adrenal Glands: Normal And on Pathological Conditions - Kodirova Nargizakhon Umarovna (European Science Publishing, 2023)
The presented review examines the normal anatomy of the adrenal glands and the features of modern methods their visualization, which is necessary for the assessment of both benign and malignant neoplasms. In particular, some of the most common formations are considered, such as adenoma, pheochromocytoma, metastatic lesions and adrenocortical cancer. For this purpose, an analysis of relevant domestic and foreign literature sources dating from 1991 to January 2021. In many cases, adrenal gland formations have distinctive features that allow characterization call them using non-invasive methods. In some cases, it is possible to suspect a malignant nature and promptly refer the patient for the necessary invasive studies. Computed tomography, especially with the use of intravenous contrast enhancement, is the main method of imaging, since in most cases suggests a nosological form of formation. Magnetic resonance imaging remains a highly sensitive method in terms of tumor detection and follow-up by size, however, the method is not very specific for determining the malignant potential of a formation. Positron emission computed tomography is also an additional method and is mainly used in the detection of malignant tumors, their differential diagnosis, detection of metastases. Ultrasound plays a limited role, however, it has great importance in diagnosis in children, especially newborns. Promising methods such as radiomics and dual-energy CT, allow for expanded imaging capabilities and improved diagnostic accuracy. Because adrenal masses are often detected incidentally on imaging performed by other reasons, it is important to interpret them correctly. This review gives the reader a broad understanding of what personal imaging may be helpful in assessing adrenal pathology and what to look for attention to radiologists and clinicians.
Keywords: adrenal glands, CT, pheochromocytoma, benign and malignant neoplasms, adrenal glands, tumors of the adrenal gland, adrenal incidentalomas, visualization adrenal gland, ultrasound,MRI, PET-CT.